Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/jid.2014.262
|View full text |Cite
|
Sign up to set email alerts
|

CD40-Mediated Amplification of Local Immunity by Epithelial Cells Is Impaired by HPV

Abstract: The interaction between the transmembrane glycoprotein surface receptor CD40 expressed by skin epithelial cells (ECs) and its T-cell–expressed ligand CD154 was suggested to exacerbate inflammatory skin diseases. However, the full spectrum of CD40-mediated effects by ECs underlying this observation is unknown. Therefore, changes in gene expression after CD40 ligation of ECs were studied by microarrays. CD40-mediated activation for 2 hours stimulated the expression of a coordinated network of immune-involved gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Indeed, hrHPV utilizes its viral proteins and exploits cellular proteins to interfere with signaling of innate immune pathways, potentially postponing the activation of an adaptive immune response (3). HPV may attenuate immune signaling at different levels in the STAT (47), IRF, and NFκB pathways (814), and has also been shown to impair IFNγ and TNFα signaling (15). Nevertheless, T cells will become activated and migrate to infected sites.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, hrHPV utilizes its viral proteins and exploits cellular proteins to interfere with signaling of innate immune pathways, potentially postponing the activation of an adaptive immune response (3). HPV may attenuate immune signaling at different levels in the STAT (47), IRF, and NFκB pathways (814), and has also been shown to impair IFNγ and TNFα signaling (15). Nevertheless, T cells will become activated and migrate to infected sites.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the combined signals are adequate to induce large changes in chemokine secretion, despite lower levels overall. Tummers et al (94) made similar observations by using genome-wide expression analysis of IFN-␥-prestimulated, CD40-ligated primary epithelial cells from foreskin, vagina, and cervix tissues. CD40 ligation produced defined networks of gene expression coordinated by early high expression of IL-8 and TNF.…”
Section: Kc Communicate With Professional Immune Cellsmentioning
confidence: 72%
“…However, CD40 ligation did increase their expression further in HPV-positive cells than in uninfected epithelial cells (94), indicating that CD40 ligation is able to partially reverse gene expression deficits caused by HPV. Similarly, lower levels of CXCL8, CXCL9, CXCL10, and RANTES (measured by ELISA) were secreted by HPV-positive rather than uninfected epithelial cells in response to IFN-␥ stimulation and CD40 ligation, and only supernatants of uninfected epithelial cells were able to increase peripheral blood mononuclear cell migration in response to IFN-␥ stimulation and CD40 ligation (94). The in vivo balance of these immune response-promoting and evasive mechanisms in epithelial cells may significantly impact HPV persistence and disease progression.…”
Section: Kc Communicate With Professional Immune Cellsmentioning
confidence: 90%
See 1 more Smart Citation
“…By contrast, IFNγ, a critical Th1 cytokine, is downregulated in infected women 213 . HPV can manipulate the quality of these infiltrates, preventing the development of effective immune responses 214 .…”
Section: Immune Interactionsmentioning
confidence: 99%